"Coffee Ring" Effect of Ag Colloidal Nanoparticles Dried on Glass: Impact to Surface-Enhanced Raman Scattering (SERS). (18th August 2021) - Šimáková, Petra; Kočišová, Eva; Procházka, Marek
Abstract : It is well known that spontaneous drying of some fluid droplets on certain solid surfaces forms a "coffee ring" pattern. In this paper, we studied "coffee ring" formation for two kinds of Ag colloidal nanoparticles (borohydride-reduced (b.-r.) and hydroxylamine-reduced (h.-r.)) and its impact on surface-enhanced Raman scattering (SERS). Optical and scanning electron microscopies were used to observe the morphology of the dried rings as well. We used 5, 10, 15, 20-tetrakis(1-methyl-4-pyridyl)porphyrin (TMPyP) as a testing SERS molecular probe. The results showed that the structure of the edge rings of dried drops of Ag colloid/TMPyP systems was different for b.-r. and h.-r. nanoparticles. The inherent limitation of our approach is inhomogeneity in particle and "hot spots" distribution, SERS signal fluctuation, and consequently low spectral reproducibility. However, in the case of h.-r. nanoparticles, it formed a structure with highly enhancing sites ("hot spots") providing enormous SERS signal of TMPyP. Higher sensitivity and the possibility of spectral mapping over the dried pattern are advantages in comparison with the measurements from colloidal suspension. Although our approach is not reliable for quantitative analytical SERS applications, it can serve as a simple, cheap, and fast prescan method, which can be easily implemented for preliminary SERS analysis.